STEM Education: A Ray of Hope for African Countries - Mutsvangwa, Andrew; Zezekwa, Nicholas (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2021)
Globally, the provision of robust education in Science, Technology, Engineering and Mathematics (STEM) is viewed as a vital ingredient in the economic success of any nation. Studies suggest a strong correlation between advances in the STEM fields and superiority of the leading economies of the world. Unfortunately, Africa seriously lags behind in the provision and delivery of quality STEM education. The purpose of this study is to review and consider the role that STEM education plays in the attainment of sustainable livelihoods for the African continent. The study also outlines and explores current challenges facing the delivery of STEM education in the schooling systems in Africa, with a sharp focus on sub-Saharan Africa. This study primarily utilized the conceptual analysis method and review of literature from research articles and scientific reports related to STEM education. The study revealed that the main issues that hinder the growth of STEM education in Africa include, the shortage of qualified STEM teachers, overcrowded classrooms, lack of resources, outdated curricula and inadequate teachers’ content and pedagogical content knowledge. In particular, of all the African students enrolled in higher education institutions, less than 25% of them are pursuing STEM qualifications, and of those students, only 30% are female. Several recommendations are suggested to the relevant stakeholders to address the challenges established in order to empower sub-Saharan Africa through solid STEM education.